The search for Kathmandu’s new landfill - Tuladhar, Bhushan (Himalayan Journal of Sciences, 2006)
The total waste of Kathmandu and Lalitpur cities can be recycled by setting up a 300 ton/day organic fertilizer plant for which an India-Nepal joint venture project is already selected. By doing this, the waste disposal problem is reduced by 80% with minimal environmental impacts, and high quality fertilizer can be generated. But despite the suggestion of different experts, the government is ignoring this simple solution to valley’s difficult problem and using Okharpauwa as landfill site following the advice of politicians who want to build a road to Okharpauwa. Experts have concluded that Okharpauwa is technically, environmentally and economically unsuitable as landfill site. Himalayan Journal of Sciences 1(1): 7-8, 2003 The full text is of this article is available at the Himalayan Journal of Sciences website